2013
DOI: 10.2140/ant.2013.7.2275
|View full text |Cite
|
Sign up to set email alerts
|

Network parametrizations for the Grassmannian

Abstract: Abstract. Deodhar introduced his decomposition of partial flag varieties as a tool for understanding Kazhdan-Lusztig polynomials. The Deodhar decomposition of the Grassmannian is also useful in the context of soliton solutions to the KP equation, as shown by Kodama and the second author. Deodhar components R D of the Grassmannian are in bijection with certain tableaux D called Go-diagrams, and each component is isomorphic to (K * ) a × (K) b for some non-negative integers a and b.Our main result is an explicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Their relationship is as follows: the matroid stratification refines the positroid stratification which refines the Schubert decomposition. In Section 3.4 we will describe the Deodhar decomposition, which is a refinement of the positroid stratification, and (as verified in [35]) is refined by the matroid stratification.…”
Section: Background On the Grassmannian And Its Decompositionsmentioning
confidence: 99%
“…Their relationship is as follows: the matroid stratification refines the positroid stratification which refines the Schubert decomposition. In Section 3.4 we will describe the Deodhar decomposition, which is a refinement of the positroid stratification, and (as verified in [35]) is refined by the matroid stratification.…”
Section: Background On the Grassmannian And Its Decompositionsmentioning
confidence: 99%
“…Postnikov showed that the positroid cells are indexed by Γ diagrams and planar bipartite graphs [22]. Each Deodhar component was shown to be indexed by so-called Go-diagrams [27] and subsequently by (generally non-planar) networks [24], which have a direct mapping to elements of the Grassmannian. The graph that represents a Deodhar component actually is in a specific matroid stratum, but each Deodhar component will have only one representative.…”
Section: Positroid Cellsmentioning
confidence: 99%
“…A graph is reduced or irreducible if it has the minimum number of independent closed paths within a given equivalence class. 24 Being defined up to equivalence transformations, reduced graphs are clearly not unique. More practically, a graph is reducible if it is possible to remove edges without changing its matroid polytope, modulo multiplicities.…”
Section: Jhep08(2014)038mentioning
confidence: 99%
See 2 more Smart Citations